2011
DOI: 10.7205/milmed-d-11-00114
|View full text |Cite
|
Sign up to set email alerts
|

The Military Emergency Tourniquet Program’s Lessons Learned With Devices and Designs

Abstract: Correct user actions (e.g., following the instructions to remove slack before twisting) led to device effectiveness, but misuse did not. Users often assumed that optimal use required more force, but this was associated with misuse. Training should include tourniquet pearls and pitfalls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 7 publications
0
22
1
3
Order By: Relevance
“…3,30 Lack of knowledge is an important barrier to EMS incorporating appropriate tourniquets into their trauma patient care tools 29 and is also a barrier to best tourniquet use.…”
Section: Discussionmentioning
confidence: 99%
“…3,30 Lack of knowledge is an important barrier to EMS incorporating appropriate tourniquets into their trauma patient care tools 29 and is also a barrier to best tourniquet use.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that self-applied CAT, researcher-applied CAT and EMT occluded popliteal flow in 16.6%, 8.3% and 75% of subjects, respectively. In 2011, Kragh et al 6 compared seven different tourniquet designs and emphasised the vital role of training, which should include pitfalls and pearls.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns centre on the ability of the CAT to control haemorrhage when applied at mid-thigh level and its effectiveness rate has been reported to range between 8.3% and 100% 2–5. The variation may be attributed to different tourniquet education and training levels of researchers, participants, combat medics, wounded soldiers and also the combat environment 2 5 6. Despite the practicality of the device, this huge variation remains largely unexplained.…”
Section: Introductionmentioning
confidence: 99%
“…Tourniquets using a wider straps or cuffs help to distribute pressure more evenly and produce lower pressure gradients, 31 are more likely to control hemorrhaging and less likely to cause damage to underlying tissue, and reduce pain compared with narrower straps and bands. 28 Practicing tourniquet application in the prehospital or educational setting requires very little equipment-normally just a device and possibly an educational model. Devices range in price from $2.75 to $45.00 and are obviously contingent on the features attached to the unit as well as the quality of the device (Table 6).…”
Section: Educational Considerations Equipmentmentioning
confidence: 99%
“…simple, lightweight, compact, and of a rugged design to withstand a multitude of environments 27,28 and should be applied before the signs of shock are evident. 14,16 In terms of device effectiveness with placement, an awareness of application to the lower extremity may present anatomical challenges due to the presence of two bones.…”
mentioning
confidence: 99%